Peningkatan Produktivitas Ikan Lele dengan Teknik Bioflok pada Komunitas Agrana (Agribisnis Anak Nagari) di Nagari Muaro Paiti Kec. Kapur IX Kab. Lima Puluh Kota - Ifmalinda Ifmalinda; Vioni Derosya; Silvia Rosa (Warta Pengabdian Andalas, 2023)
Agribusiness Anak Nagari (Agrana) is a form of business carried out by students and youth of Nagari Muaro Paiti to increase the productivity of activities, develop skills and apply fishery knowledge to the people of Nagari Muaro Paiti. The problems with current partners were inadequate fish ponds and still using bamboo as support for tarpaulin ponds, low-quality tarpaulin, unstructured pool water circulation, water pumps, and fish feed alternatives still need to be maximized, and weak marketing and post-processing capabilities harvest. Based on interviews with the head of Agrana, catfish breeders wish to develop a more productive catfish-growing business with better management. However, due to the limited skills possessed by breeders, more productive cultivation of catfish enlargement, business management, and post-harvest processing cannot be carried out. Therefore, there needs to be a transfer of technology to breeders so that breeders have various advantages in managing catfish enlargement to process yields more independently. The outputs of this program were 1) Ponds and catfish farming using the bio floc system with a diameter of 2 m: 2) Socialization of understanding of catfish farming using the bio floc system, 3) Assistance in catfish farming with the bio floc system (pond preparation, bacteria management, feed fermentation, water management, sorting catfish, and disease prevention).